Ancient India - Lal, Vinay (1998)
[Dt.:] Auf der Homepage "Manas" des Associate Professor am Historischen Institut der University of California, Vinay Lal, finden sich einführende Texte und weiterführende Verlinkungen zu vielfältigen Aspekten aus der Geschichte des indischen Subkontinents. Unter der Rubrik "Ancient India" führt der Autor in die Indus-Tal-Zivilisation der Bronzezeit mit seinen beiden bedeutenden Städten Harappa und Mohenjadaro ein. Ein zweiter Artikel widmet sich dem staatspolitischen Text Arthashastra des Brahmanen Kautilya, der im 4. Jh. v. Chr. einen Ministerposten im Mauryareich inne hatte. - [Engl.:] The Associate Professor at the UCLA History Faculty and author of many books on Indian culture and history, Vinay Lal, provides on his web site "Manas" introducing texts and continuative links that pick out a wide range of aspects on the history of the Indian subcontinent. Under the topic "Ancient India" the author inducts into The Indus civilization of the Bronze Age with its two famous cities at Mohenjadaro and Harappa. A second article focuses on the Arthashastra, a text concerning the political science, written by Kautilya (also known as Chanakya), who was a Brahmin minister in the Mauryan empire in the 4th. century BC.